PREVALENCE OF ORTHODONTIC ANOMALIES IN 6 YEARSOLD CHILDREN WITH DYSLALIA - Georgievska Jancheska, T; Tosheska Spasova, N; Stavreva, N (Faculty of Dentistry, University „Ss. Cyril and Methodius“ in Skopje and Macedonian Dental Society, 2024)
Aim of the study: The aim of our research is to determine the frequency and distribution of orthodontic anomalies in female and male children at the age of 6 who have previously been diagnosed with dyslalia. Methods: The frequency and distribution of orthodontic anomalies were analyzed in a selected sample (n=586) of boys and girls at the age of 6, all with dyslalia.The performed analysis is retrospective, on data for patients recorded in an outpatient clinic for carried out diagnostic ortho dontic-speech examinationsin the period 2015-2019 at the Public Health Institution “Center for Rehabilitation of Verbal Communication Pathology - Skopje”. The data is statistically examined, represented in tables and figures and analysed descriptively. Results: 15% of children with dyslalia had orthodontic anomalies of teeth and jaws. Most often, in as many as 50% of cases, it is about sagittal occlusion anomalies, followed by vertical occlusion anomalies (26.1%), anomalies in the dental arch es (19.3%), etc. Among children with dyslalia, girlsare more likely to have orthodontic anomalies than boys. Conclusion: The findings obtained from the research can serve for better planning and implementation of diagnostic-rehabilitation activities in relation to orthodontic anomalies and the formation of speech sounds, with the ulti mate goal of enabling, to as many children as possible, conditions for adopting clear and distinct speech sounds.
РАСПРОСТРАНЕТОСТ НА ОРТОДОНТСКИ АНОМАЛИИ КАЈ ДЕЦА НА 6ГОДИШНА ВОЗРАСТ СО ДИСЛАЛИЈА